Prospective microorganisms for the storage of apple fruitsin the conditions of the refrigerator - Pyliak, N.; Nikipelova, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To select prom ising microorganisms from the collection of cultures of microorganisms with agronomically valuable properties of ETI «Biotechnica» of NAAS for storage of apple fruits in the refrigerator.Methods. Research was conducted using generally accepted methods and methodical approaches used in microbiology and biotechnology.Results. A set of studies was conducted to isolate harmful objects that affect apple fruits when stored in refrigeration conditions. As a result of research, such pathogenic microorganisms as: Botrytis (gray fruit rot); Rhizopus (gray mold); Aspergillus (black mold); Penicillium (green mold). In laboratory conditions, a study of the antagonistic activity of promising strains of microorganisms from the collection of ETI «Biotechnica» of NAAS against phytopathogens that were isolated from affected fruits was conducted. To perform the work, fungal and bacterial strains of microorganisms with fungicidal properties were selected from the institute’s collection.Conclusions. It was established that the fungi of the genus Trichoderma showed high antagonistic activity against phytopathogens of fungal etiology. The delay in the growth of harmful objects was at the level of 90—100%. Antagonist fungal strains Gliocladium rozeum and Ampelomuces artemisia pcs. A-1, caused growth retardation zones of phytopathogens in the range of 75—80%, and Soniotirium minitans pcs. C-20 showed absolutely no antagonistic activity against phytopathogens affecting apple fruits. Among the bacterial strains, Pseudomonas aureofaciens pcs. 111 and Pseudomonas fluorenscens pcs. AR33, which suppressed the growth of phytopathogens by 85—90% due to high titers of viable cells and active metabolites. Among the bacterial strains, Pseudomonas aureofaciens pcs. 111 and Pseudomonas fluorenscens pcs. AR33, which suppressed the growth of phytopathogens by 85—90% due to high titers of viable cells and active metabolites.